Myocardial involvement is not rare in anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis/clinically amyopathic dermatomyositis: a retrospective study - Zhou, Shuang; Lai, Jinzhi; Wu, Chanyuan; Liu, Yongtai; Liu, Yingxian; Zhao, Jiuliang; Xu, Dong; Tian, Xinping; Li, Mengtao; Zhao, Yan; Wang, Yining; Wang, Qian; et al. (Frontiers in Immunology, 2022)
Objectives. Studies concerning myocardial involvement (MI) in patients with anti-melanoma differentiation-associated gene 5 antibody positive dermatomyositis/clinically amyopathic dermatomyositis (anti-MDA5 Ab+ DM/CADM) are scarce. We aimed to characterized MI in our anti-MDA5 Ab+ DM/CADM cohort and to investigate its association with prognosis. Methods. In this single-center retrospective study, anti-MDA5 Ab+ hospitalized DM/CADM patients who underwent transthoracic echocardiography (TTE) were enrolled. Myocardial involvement was diagnosed according to abnormal cardiac structure and function detected by TEE. Clinical features and cardiac examinations findings of patients with MI were analyzed. Clinical features, laboratory findings, complications and treatments were compared between MI and non-MI patients, deceased and survival patients. Logistic regression analysis was used to explore the independent risk factors for the occurrence of MI and prognostic factors for these patients. Results. Seventy-six hospitalized patients with anti-MDA5 Ab+ DM/CADM were enrolled. Twelve (15.8%) patients were diagnosed with MI. Of the 12 patients, three underwent cardiac magnetic resonance imaging (CMR) and late gadolinium enhancement (LGE) were noted for them. TEE revealed that eight (66.7%) patients had left atrial and/or ventricular enlargement, three (25.0%) had cardiac hypertrophy, six (50.0%) had diffuse ventricular wall dyskinesia and seven (58.3%) had diastolic dysfunction. Six (50.0%) patients with MI developed heart failure (HF) during treatment. Of the 12 patients, one patient died of HF caused by myocarditis, three died of infection and four died of exacerbation of rapidly progressive interstitial lung disease (RP-ILD). Logistic regression analysis revealed that dysphagia (OR 3.923, 95% CI 1.085, 14.181), NT-proBNP >600 pg/ml (OR 18.333, 95% CI 1.508, 222.875) and increased peripheral white blood cells (OR 1.201, 95% CI 1.003, 1.438) were risk factors for the occurrence of MI, but plasma albumin (OR 0.892, 95% CI 0.796, 0.999) was a protective factor. Both MI (OR 5.984, 95% CI 1.174, 30.496) and RP-ILD (OR 11.875, 95% CI 2.796, 50.411) were independent risk factors for the mortality of these anti-MDA5 Ab+ DM/CADM patients. Conclusion. Myocardial involvement is not rare and is an independent poor prognostic factor of anti-MDA5 Ab+ DM/CADM patients. Cardiac abnormalities screening is necessary for them.